Humans or machines? A systematic review of objectification at work - Bibi Zhang (21st European Association of Work and Organizational Psychology Congress, 2023)
Objectification – treating human beings as instrumental tools that are deprived of agency and experience – is inherent in many organizational practices, as some employers attempt to maximize profits by objectifying employees. However, objectification undermines target employees’ interests and well-being. This review seeks to address this dilemma by looking into relevant theories and empirical evidence with regard to workplace objectification. Specifically, this review summarizes and integrates what is known about antecedents and consequences of objectification from three different perspectives: Objectifying others, self-objectification, and experiencing objectification. We show that objectification originates in a market-pricing mode, such that people think of others and themselves in a calculative utilitarian way. This review sheds light on the dilemma of objectification by showing that people often objectify others in order to achieve their extrinsic goals, such as money and power, or to reduce subjectivity uncertainty, while thwarting the objectified targets’ fundamental control, belonging, and self-esteem needs. We provide a comprehensive framework that integrates the extant literature on objectification and identifies both theoretical and methodological recommendations. We conclude by discussing the practical implications on how to promote both employee wellness and performance (hence profitability).